Soft structures of groups and rings - Ghosh, Jayanta; Mandal, Dhananjoy; Samanta, Tapas (International Journal of Scientific World, 2017)
Concept of soft equivalence relations (classes, mappings) are introduced using the notion of soft elements. Then we redefine the notion of soft group and soft ring in a new way by using the idea of soft elements and it is seen that our definitions of soft group and soft ring are equivalent to the existing notions of soft group [2] and soft ring [1]. The notion of soft coset is presented and validated by suitable examples. We investigate some important properties like soft divisor of zero, characteristic of a soft ring etc. by considering examples. Moreover, some necessary and sufficient conditions are established for a soft ring to be a soft integral domain and soft field.